Modelling Water Age as Surrogate for Water Quality in a Distribution System: Modelling Water Age for Water Quality - Izinyon, Osadolor Christopher; Anyata, Benedict Ukeje (Biological Sciences - PJSIR, 2010)
Extended period simulation study of the water quality was made through construction of a waterCAD model of the existing Ikpoba Hill water distribution system to simulate the age of water as surrogate for water quality throughout the network. The average age of water in the network fluctuated between 0.5 and 4 h during 24 h; applying literature values of 0.00007/min and 0.00003/min for chlorine decay coefficients to the most critical time (4 h), it was indicated that the chlorine residual could degrade in the network by 1-2% only. This suggests that areas presently served by the network are not likely to suffer water quality problems on account of travel time. However, considering the age of the network, adequate attention should be paid to the possible unaccounted reasons for water problems in a network for maintain- ing the water quality integrity of the network viz., management of metering, billing and collection, and illegal connections and theft which create higher chances of drinking water contamination and outbreak of water-borne diseases.